A Unified Integral Associated with the Aleph Function (Global Journal of Science Frontier Research, 2015)
In this note we obtain a unified new integral whose integrand contains product of Aleph function and generalized multivariable polynomials having general arguments. Several integrals containing many simpler functions follow as special cases of this integral.
Keywords: aleph function; generalized polynomials; hypergeometric function; fox’s H- function